KEDUDUKAN PERATURAN NAGARI DALAM KONSTITUSI REPUBLIK INDONESIA (Lex Jurnalica, 2020)
This study describes the position of nagari regulations in the constitution of the Republic of Indonesia. Where our constitution states in the Article 18 B paragraph (2) the Constitution of the Unitary State of the Republic of Indonesia of 1945 (UUD 1945) affirms the existence of customary law community units that are recognized and respected by the state. The existence of the customary law community unit is formed based on three basic principles, namely genealogical, territorial, and / or a combination of genealogical principles and territorial principles. On this matter through the principle of regional autonomy which uses the principle of autonomy to the greatest extent in the sense of the region, it is given the authority to administer and regulate all government affairs outside the government affairs stipulated in the Law. Regions have the authority to make regional policies to provide services, increase participation, initiatives and community empowerment aimed at improving people's welfare. Wali Nagari also has the authority to form a Wali Nagari Regulation, this Wali Nagari Regulation is located as the implementing rule of the Nagari Regulation which was agreed with Bamus Nagari. as an implementing rule means the position of the Nagari Regulation is higher than the position of the Wali Nagari Regulation.